Korelasi antara Pembelajaran Berbasis Gamifikasi dengan Keaktifan Belajar Peserta Didik pada Mata Pelajaran Pendidikan Agama Islam di SMP - Nadiya Dzil Izzati; IqbalUmi Hijriyah; Safari Safari (Lembaga Sosial Rumah Indonesia, 2026)
Purpose – This study aims to examine the relationship between gamification-based learning and students’ learning activeness in the Islamic Religious Education (PAI) subject at SMP Negeri 26 Bandar Lampung.Methods – This study employed a quantitative approach with a correlational ex-post facto design. The sample consisted of 70 seventh-grade students selected through simple random sampling. Data were collected using gamification and learning activeness questionnaires developed based on measurable indicators and confirmed to be valid and reliable. Data analysis included prerequisite tests, Pearson correlation analysis, and simple linear regression.Findings – The results show a significant positive relationship between gamification-based learning and students’ learning activeness, with a correlation coefficient of r = 0.501 (moderate category), p < 0.001, R² = 0.251, and n = 70. This indicates that higher implementation of gamification elements is associated with higher levels of students’ learning activeness, including participation, attention, motivation, and interaction during PAI learning. Research Implications – This study contributes by operationalizing gamification into measurable instructional indicators and empirically examining their relationship with dimensions of learning activeness in PAI at the junior secondary level. Practically, the findings suggest that integrating gamification elements into PAI instruction may support more engaging and student-centered learning environments. However, as this study used a correlational design, causal conclusions cannot be drawn, and further experimental research is recommended.